2011
DOI: 10.1073/pnas.1117715108
|View full text |Cite
|
Sign up to set email alerts
|

A nonreplicating subunit vaccine protects mice against lethal Ebola virus challenge

Abstract: Ebola hemorrhagic fever is an acute and often deadly disease caused by Ebola virus (EBOV). The possible intentional use of this virus against human populations has led to design of vaccines that could be incorporated into a national stockpile for biological threat reduction. We have evaluated the immunogenicity and efficacy of an EBOV vaccine candidate in which the viral surface glycoprotein is biomanufactured as a fusion to a monoclonal antibody that recognizes an epitope in glycoprotein, resulting in the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 31 publications
2
60
0
Order By: Relevance
“…These results indicate that VSVΔG pseudovirion-based vaccines against EBOV elicit protective immune responses that can be independent of the production of antibodies that neutralize viral particles in cell culture assays. Consistent with our findings, protection conferred by other EBOV vaccines does not always correlate with the production of neutralizing antibodies (12,13,39,40).…”
supporting
confidence: 80%
“…These results indicate that VSVΔG pseudovirion-based vaccines against EBOV elicit protective immune responses that can be independent of the production of antibodies that neutralize viral particles in cell culture assays. Consistent with our findings, protection conferred by other EBOV vaccines does not always correlate with the production of neutralizing antibodies (12,13,39,40).…”
supporting
confidence: 80%
“…As discussed earlier, the most difficult parameter to control in this methodology is the plant material. We have expressed a variety of vaccines and therapeutic proteins using plants and the infiltration procedure we described here and obtained excellent results in all cases 4,8,14,18,[21][22][23] . These results demonstrated that the conditions we have developed are optimal for protein expression.…”
Section: Expression Of Fluorescent Proteins By Vacuum Infiltrationmentioning
confidence: 99%
“…16,19,21,22,24 These TLR agonists, or PAMP, include bacterial ligands, virus-specific ribonucleotide motifs (i.e., dsRNA), and imidazoquinoline compounds and all are currently studied as adjuvants. [1][2][3][4]6,[14][15][16][17][18][19] We have previously published results demonstrating that intranasal co-delivery with gardiquimod (GARD; TLR7 agonist) and resiquimod (R848; TLR7/8 agonist) along with Norwalk virus (NV) VLPs can elicit equivalent immune responses relative to VLPs co-delivered with cholera toxin (CT).…”
mentioning
confidence: 99%
“…In addition, we have demonstrated that a TLR3 agonist (polyinosinic:cytidylic acid (PIC)) co-delivered subcutaneously (s.c.) with Ebola immune complexes (EICs) can induce robust, systemic immunity and protection against lethal challenge with Ebola virus. 18 Recently, a TLR4 agonist (MPL, monophosphoryl lipid A) has successfully Virus-like particles (VLps) are an active area of vaccine research, development and commercialization. Mucosal administration of VLps provides an attractive avenue for delivery of vaccines with the potential to produce robust immune responses.…”
mentioning
confidence: 99%
See 1 more Smart Citation